1984
DOI: 10.1021/jm00377a013
|View full text |Cite
|
Sign up to set email alerts
|

N-Benzylpiperazino derivatives of 3-nitro-4-hydroxycoumarin with H1 antihistamine and mast cell stabilizing properties

Abstract: In a small range finding study a number of N-benzylpiperazino derivates of 3-nitro-4-hydroxycoumarin have been shown to combine potent H1-antihistamine activity with that of mast cell stabilization as demonstrated by their activity as antagonists of histamine on guinea pig ileum and by their inhibition of the release of histamine in rat passive peritoneal anaphylaxis (PPA). The most potent compound, 1-[2-hydroxy-3-[(4-hydroxy-3-nitrocoumarin-7-yl)oxy]propyl]-4- (4-chlorobenzyl)piperazine, 30, had a pA2 of 9.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Coumarins have multiple biological activities [1] , including anticoagulant [2][3][4] , anti-inflammatory [5,6] , antimicrobial [7][8][9][10][11][12] , antioxidant [13][14][15][16] , antiallergic [17][18][19][20] , anti-HIV [21] , anticancer [22][23][24][25][26][27][28] and antiviral activities [29][30][31][32] . It has been suggested that alterations in the chemical structure of coumarins could change their cytotoxic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins have multiple biological activities [1] , including anticoagulant [2][3][4] , anti-inflammatory [5,6] , antimicrobial [7][8][9][10][11][12] , antioxidant [13][14][15][16] , antiallergic [17][18][19][20] , anti-HIV [21] , anticancer [22][23][24][25][26][27][28] and antiviral activities [29][30][31][32] . It has been suggested that alterations in the chemical structure of coumarins could change their cytotoxic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The following starting compounds were prepared according to the previously described methods: piperidin-4-ylthiol [1] , 1-methylpiperidin-4-ylthiol [1,6] , 1-(3-chloropropyl)-4-phenylpiperazine [7] , 1-benzyl-4-(3-chloropropyl)piperazine [8] , 1-(4-chlorobenzyl)-4-(3-chloropropyl)piperazine [9] , 2-chloroquinoline [10] , 1-chloroisoquinoline [11] , 3-chloroisoquinoline [12] , 1,3-dichloroisoquinoline [12,13] , 1-chloro-3-methoxyisoquinoline [12] , 4-chloroquinazoline [14] , 2,4-dichloroquinazoline [15] , and 4-chlorophthalazine [16] .…”
Section: Chemistrymentioning
confidence: 99%
“…Nitrogen and oxygen containing heterocyclic compounds like pyridine, coumarin etc., are always an attraction for researchers because of its efficiency towards various pharmacological usages [6,7]. Literature survey shows that large array of coumarin derivatives possess a variety of biological activities such as antihistaminic [8], anticancer [9], antifungal [10], analgesic [11], anti-tubercular [12], antioxidant [13], antimicrobial [14], anti HIV [15], etc. They are also used as herbicides [16], neuroimaging agent [17], fluorescent whitening agent [18], organic sensitizers in dye sensitized solar cells [19], etc.…”
Section: Introductionmentioning
confidence: 99%